2023
DOI: 10.3892/etm.2023.11797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anti‑inflammatory effects of vitamin E and vitamin D on a rat model of dextran sulfate sodium‑induced ulcerative colitis

Abstract: The present study aimed to compare the clinical effects of vitamin E and vitamin D on a rat model of dextran sulfate sodium (DSS)-induced ulcerative colitis (UC), and to elucidate the underlying mechanisms associated with changes in the levels of cytokines. After successful establishment of the rat model of DSS-induced UC, prednisolone (1 mg/kg), vitamin D (50 ng) and vitamin E (6, 30 and 150 IU/kg) were orally administered for 1 week. The pharmacodynamics were evaluated by a daily combination of clinical obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…In addition, vitamin E has a major role in immunity and acts as an anti-inflammatory and antioxidant substance via the reduction of the levels of proinflammatory with elevation of anti-inflammatory cytokines, that consistent with a previous study ( Fan et al , 2023 ) found that the administration of 30 IU/kg of vitamin E can reduce the TNF-α, IL-18, IL-6, and IL-12 in rats treated with dextran sulfate sodium-induced ulcerative colitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, vitamin E has a major role in immunity and acts as an anti-inflammatory and antioxidant substance via the reduction of the levels of proinflammatory with elevation of anti-inflammatory cytokines, that consistent with a previous study ( Fan et al , 2023 ) found that the administration of 30 IU/kg of vitamin E can reduce the TNF-α, IL-18, IL-6, and IL-12 in rats treated with dextran sulfate sodium-induced ulcerative colitis.…”
Section: Discussionsupporting
confidence: 91%
“…Kaempferol, ″3,5,7-trihydroxy-2-(4-hydroxyphenyl) -4H- chromen-4-one″ is a type of flavonoids, a polyphenol and lipophilic, also known as kaempferol flavonol, kaempferide, kaempferol-3 ( Jin et al , 2023 ), it can be extracted from tea and many vegetables and fruits such as green cabbage, broccoli, olive oil, apple, chives, cucumber, strawberries, lettuce, onion, grapes, spinach, tomatoes, horseradish, and cowpea ( Alam et al , 2020 ). Studies in vivo and in vitro reported that kaempferol possesses therapeutic effects in neurodegenerative disease, colitis, and in acute and chronic inflammatory disease, including acute lung injury and postmenopausal bone loss ( Ren et al , 2019 , Liu et al , 2022 , Lim et al , 2023 ), as well as, kaempferol has a protective role in liver injury and prevents metabolic disorders, furthermore, anticancer role in breast cancer, and hepatocellular carcinoma ( Wang et al , 2019 , Sharma et al , 2021 , Fan et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted on rats that administered dextran sulfate sodium (DSS) with the intention to induce colitis and the rats were then treated with vitamin E. They noticed that the levels of pro-inflammatory cytokines reduced with 30 IU/kg αT treatment, and this included TNF-α, IL-6, IL-12 and IL-18. They also reported that αT promoted recovery and attenuated DSS-induced colitis along with the severity level of inflammation, the depth of injury and the degree of damage on the crypt of the colon tissue [57]. Moreover, another study also showed that vitamin E treatment on rats with colitis brought on by DSS had decreased the level of pro-inflammatory IL-6.…”
Section: Role Of Vitamin E In Ageing and Age-related Diseasementioning
confidence: 91%
“…Moreover, α-tocopherol and γ-tocopherol differentially regulate the intestinal microbiota in DSS-caused colitis [ 55 ]. Similarly, vitamin E (30 and 150 IU/kg) could promote the recovery of DSS-caused ulcerative colitis in rats [ 122 ]. Another investigation showed a synergistic effect of vitamin E (100 mg/kg BW) with the antioxidant trace element selenium (0.2 mg/kg BW).…”
Section: Vitamin E Supplementation and Disease Coursementioning
confidence: 99%